Mechanisms of Al3+ incorporation in MgSiO3 post-perovskite at high pressures - Zhang, Feiwu; Organov, A. (Elsevier Science BV, 2006)
Aluminum is the fifth most abundant element in the Earth's mantle, yet its effect on the physical properties of the newlyfound MgSiO3 post-perovskite (PPv), the major mineral of the Earth's D" layer, is not fully known. In this paper, large-scaleab initio simulations based on density functional theory (DFT) within the generalized gradient approximation (GGA) havebeen carried out in order to investigate the substitution mechanism of Al3+ into PPv at high pressures. We have examinedthree types of Al substitution in PPv: 6.25 mol% Al substitution via a charge-coupled mechanism (CCM), 6.25 mol% Alsubstitution via oxygen-vacancy mechanism (OVM), and an oxygen-vacancy Si-free end member Mg2Al2O5. For both theCCM and OVM, five models, where the Al atoms were put in different positions, were simulated at various pressures in therange 10–150 GPa. Our calculations show that the most favorable mechanism is a charge-coupled substitution where Al3+replaces the next-nearest-neighbor cation pairs in the PPv structure. The calculated zero-pressure bulk modulus of Al-bearingPPv is 3.15% lower than that of the Al-free PPv. In agreement with previous works, we find that the incorporation of Al2O3slightly increases the post-perovskite phase transition pressure, with the Al partition coefficient K=2.67 at 120 GPa and3000 K.